Impact of Autoantibodies against Glycolytic Enzymes on Pathogenicity of Autoimmune Retinopathy and Other Autoimmune Disorders - Adamus, Grazyna (Frontiers in Immunology, 2017)
Autoantibodies (AAbs) against 4 glycolytic enzymes: aldolase, α-enolase, glyceraldehyde-3-phosphate dehydrogenase, and pyruvate kinase are prevalent in sera of patients with blinding retinal diseases, such as paraneoplastic (cancer-associated retinopathy, CAR) and non-paraneoplastic autoimmune retinopathies as well as in many other autoimmune diseases. CAR is a degenerative disease of the retina characterized by sudden vision loss in patients with cancer and serum anti-retinal autoantibodies. In this review we discuss the widespread serum presence of anti-glycolytic enzyme AAbs and their significance in autoimmune diseases. There are multiple mechanisms responsible for antibody generation, including the innate anti-microbial response, anti-tumor response, or autoimmune response against released self-antigens from damaged, inflamed tissue. Autoantibodies against enolase, GADPH, and aldolase exist in a single patient in elevated titers, suggesting their participation in pathogenicity. The lack of restriction of AAbs to one disease may be related to an increased expression of glycolytic enzymes in various metabolically active tissues that triggers an autoimmune response and generation AAbs with the same specificity in several chronic and autoimmune conditions. In CAR, the importance of serum anti-glycolytic enzyme AAbs had been previously dismissed, but then the retina may be without pathological consequence until a failure of the blood-retinal barrier function, which would allow pathogenic AAbs access to their retinal targets, ultimately leading to damaging effects.